STRATEGI PEMASARAN KEDAI KOPI UNTUK MENINGKATKAN VOLUME PENJUALAN (Studi Kasus Pada Serumah Kopi, Cikutra Barat, Kota BanDUNG) - Haidar, Faris Julda; Wiyono, Sulistyodewi Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Supplier performance plays an important role in ensuring the availability of supply goods that will affect the Serumah Kopi is a coffee shop that mainly sells coffee. Several marketing activities have been carried out to increase sales volume, but the sales volume of the coffee shop is still low. The objectives of this study are to 1) understand the current marketing management of Serumah Kopi Coffee Shop, 2) identify alternative marketing strategies and the best marketing strategy for Serumah Kopi Coffee Shop. The research method used is qualitative with a case study technique. Primary and secondary data were collected through observation, interviews and literature studies. Data were analyzed using strength, weakness, opportunity & threat (SWOT) and Quantitative Strategic Planning Matrix (QSPM) analysis. The results of the study show that there are seven alternative strategies 1) Providing testers / free trial vouchers to the local community, 2) Consistently creating creative content by highlighting characteristics, 3) Selling through all online food delivery platforms as well as participating in promos from each online food delivery platform , 4) Providing the accuracy of the guarantee of suitability of taste & timeliness of making orders, 5) Providing games (cards, chess, etc.) and wifi to support consumer needs. With an alternative priority strategy is the first strategy.